2015
DOI: 10.1093/jxb/erv138
|View full text |Cite|
|
Sign up to set email alerts
|

ICE1 of Poncirus trifoliata functions in cold tolerance by modulating polyamine levels through interacting with arginine decarboxylase

Abstract: Highlight: ICE1 of Poncirus trifoliata (L.) Raf. plays a positive role in cold tolerance and modulates polyamine synthesis by interacting with arginine decarboxylase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 73 publications
4
64
0
5
Order By: Relevance
“…Higher SOD, CAT, APX and GR activities were measured in cold-treated DX indicating that higher efficiency in the balance of ROS production. Furthermore, the transriptome results also showed the up-regulation of nonenzymic antioxidants in DX, including tocopherol, GSH, and polyamine, which have been reported to function in elevating stress tolerance [9, 32]. These results will help in broader understanding of the enhanced cold tolerance in DX partially resulted from ROS pathways modulation.…”
Section: Discussionmentioning
confidence: 77%
“…Higher SOD, CAT, APX and GR activities were measured in cold-treated DX indicating that higher efficiency in the balance of ROS production. Furthermore, the transriptome results also showed the up-regulation of nonenzymic antioxidants in DX, including tocopherol, GSH, and polyamine, which have been reported to function in elevating stress tolerance [9, 32]. These results will help in broader understanding of the enhanced cold tolerance in DX partially resulted from ROS pathways modulation.…”
Section: Discussionmentioning
confidence: 77%
“…It is also demonstrated that putrescine plays a role in maintaining ROS homeostasis by regulating the antioxidant system to elevate abiotic stress tolerance (Liu et al ., ; Wang et al ., ; Song et al ., ). Accumulation of putrescine activates antioxidant enzymes such as superoxidase dismutase and catalase to eliminate redundant ROS under cold stress in tobacco and lemon (Huang et al ., ). In potato, freezing‐tolerant genotypes accumulated more putrescine to response to cold stress, while sensitive genotypes did not (Figure ), suggesting that putrescine is involved in freezing tolerance of potato.…”
Section: Discussionmentioning
confidence: 97%
“…These findings support the inference that ICE1 has a function in regulating the expression of CBF and COR genes under cold stress, and that ICE1 and ICE2 together contribute even more to the cold‐induced gene expression and freezing tolerance. In addition, a role of ICE1 homologs in cold stress response has been observed in many plant species such as rice, tomato, Zea mays, Chrysanthemum dichrum , Chinese wild Vitis amurensis, Pyrus ussuriensis, Poncirus trifoliata , and Cucumis sativus (Liu et al 2010; Feng et al 2013; Xu et al 2014; Huang et al 2015a, 2015b; Lu et al 2017; Zhang et al 2017).…”
Section: Accession Numbermentioning
confidence: 99%